Revisiting Anti-tuberculosis Therapeutic Strategies That Target the Peptidoglycan Structure and Synthesis - Catalão, Maria João; Filipe, Sérgio R.; Pimentel, Madalena (Frontiers in Microbiology, 2019)
One of the leading causes of infectious diseases death worldwide is tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb). The biosynthesis of the mycobacterial cell wall (CW) is an area of significant research interest, as several of the antibiotics used to treat TB target biosynthesis pathways of essential CW components. The main feature of the mycobacterial CW is an intricate structure, the mycolyl-arabinogalactan-peptidoglycan (mAGP) complex responsible for its innate resistance to many commonly used antibiotics and involved in virulence. A hallmark of mAGP is its unusual peptidoglycan (PG) layer which has subtleties that play a key role in virulence by enabling pathogenic species to survive inside the host and resist antibiotic pressure. This dynamic and essential structure has not been targeted by anti-TB therapy as Mtb is considered innately resistant to most beta-lactams antibiotics due to a highly active beta-lactamase (BlaC) that efficiently hydrolyses many beta-lactams drugs to render them ineffective. The emergence of multidrug- and extensive drug-resistant strains to the available antibiotics has become a serious health threat, places an immense burden on health care systems and poses particular therapeutic challenges. Therefore, it is crucial to explore additional Mtb vulnerabilities that can be used to combat TB. Remodelling PG enzymes that catalyse biosynthesis and recycling of the PG are essential and are therefore attractive targets for novel antibiotics research. This article reviews PG as an alternative antibiotic target for TB treatment, how Mtb has developed resistance to currently available antibiotics directed to PG biosynthesis, and the potential of targeting this essential structure to tackle TB by attacking alternative enzymatic activities involved in Mtb PG modifications and metabolism.